Physical activity and health promoting lifestyle among bachelor of nursing students in Malaysia - Soh, Kim Geok; Japar, Salimah; Swee, Leong Ong; Soh, Kim Lam (Advanced Scientific Research, 2018)
Promoting healthy lifestyle among nurses is important because they play a crucial role in health promotion. The aims of this study are to assess the physical activity level and health-promoting lifestyle among Bachelor of nursing students in Malaysia. This study involved 66 student nurses who are currently pursuing a Bachelor degree in the local government universities. The YAMAX Digi-Walker pedometer was used to measure physical activity level, while the Health-promoting Lifestyle Profile II questionnaire was used to measure the nursing student’s health-promoting lifestyle. The HPLP II consists of six sub-scales which include health responsibility, physical activity, nutrition, spiritual growth, interpersonal relations, and stress management. Results showed that majority of the Bachelor of nursing students were categorised as “somewhat active” and lower with the mean of 7487.88±SD1900.75 step taken per day. Results of Health-Promoting Lifestyle Profile II showed that the Bachelor of nursing students are reported to have a positive health-promoting lifestyle with an overall mean score of 2.61±SD0.36. The highest mean score was reported in the spiritual growth with a score of 3.07±SD0.40, followed by interpersonal relations with a score of 2.93±SD0.40, and stress management with mean a score of 2.67±SD0.41. This study has discovered worrying signs of low physical activities level among the Bachelor of nursing students in two universities in Malaysia which may need immediate attention by the health care authorities. Immediate remedial is recommended to overcome the current status of physical activities level among the nursing students which may have an impact on the future health of the Malaysian general populations.